Intratumoral neoadjuvant immunotherapy based on the BO-112 viral RNA mimetic. (31st December 2023) - Alvarez, Maite; Molina, Carmen; Garasa, Saray; Ochoa, Maria C.; Rodriguez-Ruiz, Maria E; Gomis, Gabriel; Cirella, Assunta; Olivera, Irene; Glez-Vaz, Javier; Gonzalez-Gomariz, Jose; luri-Rey, carlos; azpilikueta, arantza; et al.
ABSTRACT: BO-112 is a poly I:C-based viral mimetic that exerts anti-tumor efficacy when intratumorally delivered in mouse models. Intratumoral BO-112 synergizes in mice with systemic anti-PD-1 mAbs and this combination has attained efficacy in PD1-refractory melanoma patients. We sought to evaluate the anti-tumor efficacy of BO-112 pre-surgically applied in neoadjuvant settings to mouse models. We have observed that repeated intratumoral injections of BO-112 prior to surgical excision of the primary tumor significantly reduced tumor metastasis from orthotopically implanted 4T1-derived tumors and subcutaneous MC38-derived tumors in mice. Such effects were enhanced when combined with systemic anti-PD-1 mAb. The anti-tumor efficacy of this neoadjuvant immunotherapy approach depended on the presence of antigen-specific effector CD8 T cells and cDC1 antigen-presenting cells. Since BO-112 has been successful in phase-two clinical trials for metastatic melanoma, these results provide a strong rationale for translating this pre-surgical strategy into clinical settings, especially in combination with standard-of-care checkpoint inhibitors.